2023
DOI: 10.3390/pharmaceutics15041195
|View full text |Cite
|
Sign up to set email alerts
|

Abies holophylla Leaf Essential Oil Alleviates Allergic Rhinitis Based on Network Pharmacology

Abstract: Abies holophylla is an evergreen coniferous species that has been widely used for treating pulmonary diseases and colds. Previous research has demonstrated the anti-inflammatory effect of Abies species and the anti-asthmatic activities of Abies holophylla leaf essential oil (AEO). As asthma and allergic rhinitis (AR) share pathophysiology and pharmacotherapeutic interventions, AEO inhalation can also ameliorate upper respiratory allergic diseases. This study explored the protective effects of AEO on AR with ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 71 publications
(78 reference statements)
0
8
0
Order By: Relevance
“…A leaf EO of A. holophylla reduced asthma symptoms in a mouse model and inhibited the IL-17 signaling pathway, as well as the activity of NF-kB [ 234 ]. The same mechanism was shown to explain the benefits of the same EO in a murine model of allergic rhinitis [ 235 ].…”
Section: Pharmacological Interest Of Pinaceae Eosmentioning
confidence: 74%
“…A leaf EO of A. holophylla reduced asthma symptoms in a mouse model and inhibited the IL-17 signaling pathway, as well as the activity of NF-kB [ 234 ]. The same mechanism was shown to explain the benefits of the same EO in a murine model of allergic rhinitis [ 235 ].…”
Section: Pharmacological Interest Of Pinaceae Eosmentioning
confidence: 74%
“…Numerous studies have observed that PM 2.5 and PM 10 can induce varying degrees of impairment in the nasal epithelial barrier, leading to a reduction in ZO-1, occludin, and claudin-1 expression. [144][145][146][147][148][149][150] Meanwhile, DEP causes nasal epithelial leakage by downregulating ZO-1, occludin, and claudin-1 while upregulating claudin-8 in IT-derived HNECs and BALB/c mice. 151,152 Cigarette smoke also impairs barrier by reducing ZO-1 and JAM-A expression in sinus-derived HNECs.…”
Section: Ta B L E 3 (Continued)mentioning
confidence: 99%
“…138 Although it remains unclear whether dexamethasone (Dex) can effectively alleviate symptoms in CRS, there is evidence suggesting that Dex can reverse the impairment of TJs in IL-13-induced primary HNECs 93 and PM 10 -induced RPMI2650 cells. 146,147 Meanwhile, oral administration 136 and nasal aerosol inhalation 146,147 while preventing ZO-1 degradation in the nasal epithelium of OVAinduced AR mice. 138 An increasing number of studies have demonstrated the potential efficacy of traditional Chinese medicine (TCM) in treating CRS 170 and AR.…”
Section: Response To Medical Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies [9] have shown that TCM has long-term e cacy in alleviating AR symptoms. For example, Magnoliae Flos, Hedysarum Multijugum Maxim and other traditional Chinese medicines were used to treat rhinitis in ancient times [10], and modern pharmacological studies have con rmed that these drugs hold the effect to treat rhinitis.…”
Section: Introductionmentioning
confidence: 99%